STRATEGI EKSPOR PRODUK UMKM KE PASAR INTERNASIONAL: STUDI KASUS UMKM MOLRING SARI RASA TASIKMALAYA DALAM PENETRASI PASAR MALAYSIA - Hasna Najwa Sabrina; Riezka Putri Imanda; Rosiana Dewi; Tiara Apriani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This research aims to analyze the export strategy of Molring Sari Rasa Tasikmalaya UMKM in penetrating the Malaysian market. Using a qualitative descriptive approach, data was obtained through direct collaboration with business owners and related literature. The export strategy includes cooperation with business owners, utilization of personal networks, and promotion via social media. The results show that this approach is effective in reaching Indonesian consumers in Malaysia, with a simple export process from communication, packaging, to delivery and payment through Wise services. This research confirms the potential of UMKM to penetrate international markets using digital strategies and social networks, and offers a practical export model for start-up UMKM.